Psychological impact on patients with oral cancer before undergoing resection and free flap reconstruction surgery - Satoshi Yamaguchi; Kento Kaminogo; Tatsuya Tokura; Hiroyuki Kimura; Shinichi Kishi; Noriyuki Yamamoto; Norihisa Ichimura; Naoto Toyama; Yoshiro Koma; Naoka Kouyama; Norio Ozaki; Hideharu Hibi (Oral Oncology Reports)
Objective: The psychological state of patients with advanced oral cancer should be evaluated as the disease and its treatment are considered to impose immense psychological burden. This study aimed to clarify the psychological state of patients with oral cancer immediately prior to their surgery. Materials and methods: This study included patients with oral cancer scheduled for a free flap reconstruction surgery between February 2017 and October 2020. The Japanese version of the Impact of Event Scale-Revised (IES-R), a self-administered assessment used to screen post-traumatic stress disorder (PTSD) symptoms, was used to investigate their psychological status. Results: The self-administered IES-R questionnaire was completed by 34 patients. The median IES-R score was 19 points (8−38), and the scores did not differ by background characteristics. Of the 34 patients, 14 (41.2%) had a cutoff value score of 25 points or higher. Discussion: PTSD symptoms may occur in some patients with advanced oral cancer prior to surgery. Support is required to alleviate anxiety regarding the patient's treatment, subsequent life, and prognosis.